Sphincteroplasty for anal incontinence - Pescatori, Lorenzo Carlo (Oxford University Press, 2014)
Sphincteroplasty (SP) is the operation most frequently performed in patients suffering from moderate-to-severe anal incontinence (AI) who do not respond to conservative treatment. Other costly surgeries, such as artificial bowel sphincter (ABS) and electro-stimulated graciloplasty, have been more or less abandoned due to their high morbidity rate. Minimally invasive procedures are widely used, such as sacral neuromodulation and injection of bulking agents, but both are costly and the latter may cure only mild incontinence. The early outcome of SP is usually good if the sphincters are not markedly denervated, but its effect diminishes over time. SP is more often performed for post-traumatic than for idiopathic AI. It may also be associated to the Altemeier procedure, aimed at reducing the recurrence rate of rectal prolapse, and may be useful when AI is due either to injury to the sphincter, or to a narrowed rectum following the procedure for prolapse and haemorrhoids (PPH) and stapled transanal rectal resection (STARR). The outcome of SP is likely to be improved with biological meshes and post-operative pelvic floor rehabilitation. SP is more effective in males than in multiparous women, whose sphincters are often denervated, and its post-operative morbidity is low. In conclusion, SP, being both low-cost and safe, remains a good option in the treatment of selected patients with AI.